HEAVY METALS IN THE BIVALVE ATRINA SEMINUDA (LAMARCK, 1819) (PTERIOIDA) IN DIFFERENT STATES OF GONADAL MATURATION FROM GUAYACÁN, VENEZUELA - Lemus, Mairin (2021)
Heavy metals in male and female specimens of the bivalve Atrina seminuda (Lamarck, 1819) were evaluated. The organisms were collected from Guayacán, Sucre State, Venezuela. The concentrations Cu, Cd, Cr, Ni, Pb, Fe and Zn were determined in the tissues: gonad (G), muscle (M), hepatopancreas (H) and rest (R) by inductively coupled plasma emission spectroscopy (ICP-OES) coupled to a Perkin Elmer brand equipment. The gonadosomatic index (IGS) showed significant differences (Kw= 31.68; P < 0.01), showing its highest value in February (19.67 ± 0.43) and the lowest in June (13.26 ± 0.43). Metal concentrations showed significant differences between the analyzed tissues; showing in general a greater accumulation of metals in the H and R. Significant monthly variations of metals were shown in the tissues with the highest concentrations of Cu, Cd, Cr, Ni and Zn between April and May. The PCA analysis determines that IGS is associated with the incorporation of metals. These monthly variations in the metals analyzed can be explained by the bioavailability of these elements partly determined by the high levels of chlorophyll a, which is characteristic of the outcrop in the northeastern area of the country and by the variation in the reproductive cycle of the species studied.